2022
DOI: 10.1111/ahe.12851
|View full text |Cite
|
Sign up to set email alerts
|

Skull anatomy of the endangered Patagonian huemul deer(Hippocamelus bisulcus)

Abstract: Studies of the normal skull anatomy of the Patagonian Huemul deer are scarce.Currently, the findings of bone lesions in the skull associated with metabolic imbalances are frequent in the literature. The objective of this study was to provide anatomical and morphometric data of the cranium and facies including a morphofunctional interpretation as a reference for clinical, ecomorphological and educational purposes.Five skulls were described, measured, scanned and digitally reconstructed. The presence of a caudal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This foramen, which is present in pigs and ruminants, has been described in classical sources [1,21,32] as the equivalent of the f round foramen, orbital fissure and trochlear foramen in the horse. In deer (Hippocamelus bisulcus), the ORF is divided into two compartments, dorsal and ventral [33]. In the present study, the ORF was observed as a smooth-walled canal with a triangular intracranial opening and a vertical oval orbital opening, bounded by the pre-basisphenoid bone as described in the literatüre (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…This foramen, which is present in pigs and ruminants, has been described in classical sources [1,21,32] as the equivalent of the f round foramen, orbital fissure and trochlear foramen in the horse. In deer (Hippocamelus bisulcus), the ORF is divided into two compartments, dorsal and ventral [33]. In the present study, the ORF was observed as a smooth-walled canal with a triangular intracranial opening and a vertical oval orbital opening, bounded by the pre-basisphenoid bone as described in the literatüre (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, the extension of the frontal sinus within the pedicles—the cylindrical excrescences of the frontal bone—possibly suggests their function in absorbing and releasing mechanical energy, as has been described in the goat (Alsafy et al, 2021). This function of mechanical dissipation by the frontal sinus is usually greater in skulls with a convex frontal bone (Curtis et al, 2015), as reported in the Patagonian huemul deer (Núñez‐Cook et al, 2022).…”
Section: Discussionmentioning
confidence: 79%
“…Despite the clinical importance and the presentation of diseases that involve the paranasal sinuses and nasal conchae in our deer study, little is known of its anatomy. In previous anatomical descriptions, we have reported differences in thickness between bones of the appendicular skeleton and bones of the neurocranium (Núñez-Cook et al, 2022), suggesting a possible unequal nutritional food chain among the geographic locations inhabited by the individuals studied. Following from this study, what the morphological effect of nutritional deficiency has on the nasal cavity, nasal conchae and paranasal sinuses is currently unknown.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations